2015
DOI: 10.1007/s00540-015-2040-x
|View full text |Cite
|
Sign up to set email alerts
|

Pain sensitivity: a feasible way to predict the intensity of stress reaction caused by endotracheal intubation and skin incision?

Abstract: Pain tolerance had a significant relationship with stress response during intubation and skin incision. We may initially use pain tolerance to direct opioid usage in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“… 33 However, a previous study suggested that the patient’s response to pain after anesthesia induction has a significant relationship with preoperative pain tolerance. 28 These findings support our assumption that the withdrawal reaction is associated with the patients’ pain-related symptoms and EA in this study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“… 33 However, a previous study suggested that the patient’s response to pain after anesthesia induction has a significant relationship with preoperative pain tolerance. 28 These findings support our assumption that the withdrawal reaction is associated with the patients’ pain-related symptoms and EA in this study.…”
Section: Discussionsupporting
confidence: 90%
“… 26 Moreover, it has been demonstrated that an increased pain score for supra-threshold noxious stimulation has a better predictive value than pain thresholds. 26 , 27 Furthermore, authentic pain stimuli reflect pain tolerance more closely than pain threshold, 28 suggesting that they can be utilized as a representative of supra-threshold noxious stimuli. In human beings, the peripheral veins are innervated by polymodal nociceptors, which mediate the signal transmission for the injection pain of certain agents.…”
Section: Discussionmentioning
confidence: 99%
“…Anesthetic requirements might be affected by individual nociception during the surgical procedure. Wang et al [22] reported that patients' preoperative pain sensitivity was correlated with their stress response during endotracheal intubation and skin incision. Pain tolerance was negatively correlated with changes in BP, HR, and plasma norepinephrine level before and after intubation and skin incision.…”
Section: Discussionmentioning
confidence: 99%
“…Anesthetic requirements might be affected by individual nociception during the surgical procedure. Wang et al [ 12 ] reported that patients’ preoperative pain sensitivity was correlated with their stress response during endotracheal intubation and skin incision. Pain tolerance was negatively correlated with changes in blood pressure (BP), heart rate (HR), and plasma norepinephrine level before and after intubation and skin incision.…”
Section: Introductionmentioning
confidence: 99%